Alcohol use disorder and its associated factors among patients with psychiatric conditions admitted at Kabale regional referral hospital, Southwestern Uganda. A cross-sectional study. - Twinomuhwezi , Benja; Tweheyo Otwine, Anne (Student's Journal of Health Research Africa, 2025)
Background Alcohol use disorder has been a public health concern globally. Although research in this area has been conducted, most studies have been conducted in high-income countries, with less research in low-income countries. This study sought to determine the prevalence of Alcohol Use Disorder (AUD) and its associated factors among patients with psychiatric conditions admitted at Kabale regional referral hospital, Southwestern Uganda. Methodology The study employed a cross-sectional design, utilizing a quantitative approach that involved collecting quantitative data. The statistical analyses were done using SPSS version 25. Results Results from this study revealed that 150 (63.6%) were male and 86 (36.4%) were female, and most participants, 132 (55.9%), scored between 0 and 7, indicating low-risk or non-hazardous alcohol use. An additional 58 participants (24.6%) scored 8–15, placing them at increasing risk and suggesting a pattern of alcohol consumption that could lead to health problems. Twelve participants (5.1%) scored between 16 and 19, categorizing them as higher risk, which is typically associated with harmful drinking behaviors. Notably, 34 participants (14.4%) scored 20 or above, indicating a probable alcohol use disorder (AUD). The study further revealed that factors like being male (p < 0.001), being raised by a single parent (p = 0.031), and tertiary education (p = 0.022) were significantly associated with AUD. Other factors were not significantly associated. Conclusion The study concludes that 14.4% of mental patients had likely AUD, as determined by the AUDIT instrument. Recommendation Mental health facilities should regularly use validated and standardized tools like the AUDIT to screen for AUD. There is also a need for community sensitization programs by the government, focusing on the risks of early alcohol use initiation and its long-term mental health consequences.